2019
DOI: 10.1128/aem.00739-19
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Lipopeptide Paenibacterin Disrupts Desiccation Resistance in Salmonella enterica Serovars Tennessee and Eimsbuettel

Abstract: Salmonella enterica is increasingly linked to disease outbreaks associated with consumption of low-water-activity (low-a w ) foods. Persistence of the pathogen in these foods was attributed to its ability to implement desiccation resistance mechanisms. Published knowledge about methods that disrupt desiccation resistance in S. enterica is lacking. We hypothesize that strong membrane-active compounds disrupt the desiccation resistance that S. enterica may acquire in low-a w foods or environments. The newly disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…The longest survival of all three species were detected at 5 °C, where the bacteria were not inactivated after 300 days and showed a maximum reduction of 4 logs [ 135 ]. Other serotypes, S. Tennessee and S. Eimsbuettel were detectable after 72 h on plastic at 22 °C and 40% RH according to a study by Abdelhamid et al [ 149 ]. The titer reduction was 1-log after 72 h [ 149 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longest survival of all three species were detected at 5 °C, where the bacteria were not inactivated after 300 days and showed a maximum reduction of 4 logs [ 135 ]. Other serotypes, S. Tennessee and S. Eimsbuettel were detectable after 72 h on plastic at 22 °C and 40% RH according to a study by Abdelhamid et al [ 149 ]. The titer reduction was 1-log after 72 h [ 149 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other serotypes, S. Tennessee and S. Eimsbuettel were detectable after 72 h on plastic at 22 °C and 40% RH according to a study by Abdelhamid et al [ 149 ]. The titer reduction was 1-log after 72 h [ 149 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, our goal was to explore methods to overcome desiccation-resistant Salmonella without excessive processing. In a previous study, we found that a newly discovered microbial lipopeptide, paenibacterin, disrupted the desiccation resistance in S. enterica and rendered the pathogen sensitive to desiccation [ 8 ]. Paenibacterin caused intracellular potassium leakage, increased the cytoplasmic membrane permeability, decreased the biosynthesis of the osmoprotectant trehalose, and downregulated the expression of desiccation-related genes in desiccation-adapted S. enterica .…”
Section: Introductionmentioning
confidence: 99%
“…Such synergistic interaction, also known as hurdle approach, aims to get maximum lethality against foodborne pathogens ( Leistner, 2000 ). For example, sequential application of the lipopeptide paenibacterin and desiccation stress resulted in significant population reduction (1.5–1.9 log CFU/ml) of S. enterica serovars compared to desiccation stress alone (<0.1 log CFU/ml) ( Abdelhamid and Yousef, 2019 ). Another example was that three antimicrobials, nisin A, lactoperoxidase, and reuterin, synergized to control L. monocytogenes and S. aureus in a dairy product with 4-log reduction after incubation at 10 °C for 12 days, compared to that reduction by any of the two antimicrobials ( Arqués et al., 2008 ).…”
Section: Control Of Microbial Growthmentioning
confidence: 99%